Photoredox catalysis in nickel-catalyzed C–H functionalization - Mantry, Lusina; Maayuri, Rajaram; Kumar, Vikash; Gandeepan, Parthasarathy (Beilstein Journal of Organic Chemistry, 2021)
Catalytic C‒H functionalization has become a powerful strategy in organic synthesis due to the improved atom-, step- and resource economy in comparison with cross-coupling or classical organic functional group transformations. Despite the significant advances in the metal-catalyzed C‒H activations, recent developments in the field of metallaphotoredox catalysis enabled C‒H functionalizations with unique reaction pathways under mild reaction conditions. Given the relative earth-abundance and cost-effective nature, nickel catalysts for photoredox C‒H functionalization have received significant attention. In this review, we highlight the developments in the field of photoredox nickel-catalyzed C‒H functionalization reactions with a range of applications until summer 2021.
Keywords: C–H activation; functionalization; nickel; photocatalysts; photoredox; visible light